(untitled) (مجلة ديالى للبحوث الانسانية, 2022)
An assessment of Testing Vocabulary in (RECI) Book -1- for the Fifth Grade of the primary stage Learning vocabulary is a lengthy and complex process which requires adequate mastery of form, meaning and usage . It requires constant practice on the part of the learner and continuous assessment on the part of the teacher . Vocabulary tests are intended to measure the comprehension and production of words used in speaking and writing . The type of vocabulary test chosen is related to how we teach it . For these reason’s , this study has been conducted to investigate the techniques of testing vocabulary for (RECL) Book -1- for the fifth grade of the primary stage . A test of five parts has been conducted to a sample of (50) pupils at Al-Muqdadia schools for boys and girls for the academic year 2009-2010 to fulfill the aims of the study . The test is exposed to a jury of specialists in the filed of English language teaching and linguistics who have agreed on its validity for administration. The test reliability is computed by using the correlation coefficient of test-retest. Chi – square has been used to find out the statistical significance of differences between each two techniques of testing vocabulary . After analyzing the data statistically , it has been found out that the odd one out and classification techniques are considered more effective